Kepemimpinan dan Praktek Manajerial dalam Pendidikan Islam (Hubungan Kepemimpinan dengan Organisasi Sekolah) - yani, indra (Maliki Interdisciplinary Journal, 2026)
Islamic education emphasizes a balance between intellectual intelligence and character development. In this context, leadership plays an important role as both a director and a role model for school members. This article aims to examine the relationship between leadership and school management effectiveness in improving the quality of education. The research method uses a literature study by examining the Quran, hadiths, books, and scientific articles. The results show that visionary, just, and communicative Islamic leadership is able to strengthen school management thru targeted planning, implementation, and supervision. Thus, the quality of Islamic education is not only determined by academic aspects, but also by the integration of moral and spiritual values thru leadership example.